2007
DOI: 10.1086/515388
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy Clusters Associated with Short GRBs. II. Predictions for the Rate of Short GRBs in Field and Cluster Early‐Type Galaxies

Abstract: We determine the relative rates of short GRBs in cluster and field early-type galaxies as a function of the age probability distribution of their progenitors, P() / n . This analysis takes advantage of the difference in the growth of stellar mass in clusters and in the field, which arises from the combined effects of the galaxy stellar mass function, the early-type fraction, and the dependence of star formation history on mass and environment. This approach complements the use of the early-to late-type host ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…We have shown that current Swift data seem to point towards a dual nature of SGRB formation: low‐ z SGRBs may arise from the coalescence of DNSs forming in GCs through dynamical collisions, whereas high‐ z bursts can represent the end‐result of DNS mergers born in the field from primordial massive binary stars. A way to falsify this bimodality is by considering the correlation between SGRBs and the host galaxy type (Gal‐Yam et al 2005; Berger et al 2007b; Shin & Berger 2007; Zheng & Ramirez‐Ruiz 2007). We expect that SGRBs from the GC channel should be found preferentially in early‐type galaxies where the bulk of GCs resides, although we cannot completely exclude a few in spirals.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that current Swift data seem to point towards a dual nature of SGRB formation: low‐ z SGRBs may arise from the coalescence of DNSs forming in GCs through dynamical collisions, whereas high‐ z bursts can represent the end‐result of DNS mergers born in the field from primordial massive binary stars. A way to falsify this bimodality is by considering the correlation between SGRBs and the host galaxy type (Gal‐Yam et al 2005; Berger et al 2007b; Shin & Berger 2007; Zheng & Ramirez‐Ruiz 2007). We expect that SGRBs from the GC channel should be found preferentially in early‐type galaxies where the bulk of GCs resides, although we cannot completely exclude a few in spirals.…”
Section: Discussionmentioning
confidence: 99%
“…The first short GRB with an afterglow detection, GRB 050509b, was most likely associated with a galaxy cluster at z = 0.225 (Gehrels et Since the stellar populations in galaxy clusters are systematically older than in field galaxies, the fraction of short GRBs in clusters can be used as an indicator of the age distribution (Shin & Berger 2007). At present, the fraction of short GRBs in clusters appears to be ∼ 10% (Berger et al 2007b), at the low end of the fraction of cosmic stellar mass in clusters of about 10 − 20% (Fukugita, Hogan & Peebles 1998; Eke et al 2005).…”
Section: Galaxy Clustersmentioning
confidence: 99%
“…If this excess of intervening systems is real, it should be possible to find an excess of GRB field galaxies around GRB positions, although a preliminary study has revealed no anomalous clustering of galaxies (in comparison with distribution of quasar) at the estimated median redshift of about 0.3 around GRB line of sights [17]. Furthermore, it has been proposed that the majority of shortduration GRBs in early-type galaxies will occur in clusters and three such relationships have been already found [38].…”
Section: Discussionmentioning
confidence: 97%